2007
DOI: 10.3171/foc-07/12/e13
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of glomus jugulare tumors: a historical perspective

Abstract: ✓ Glomus jugulare tumors are rare, slow-growing vascular lesions that arise from the chief cells of the paraganglia within the jugular bulb. They can be associated with the tympanic branch of the glossopharyngeal nerve (Jacobsen nerve) or the auricular branch of the vagus nerve (Arnold nerve) and are also referred to as chemodectomas or nonchromaffin paragangliomas. Optimal treatment of these histologically benign tumors remains controversial. Surgery remains the treatment of choice, but can carry high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…The second aspect is that the consequences of injury to the low cranial nerves, which are typically involved in GJT, are very severe. [22]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second aspect is that the consequences of injury to the low cranial nerves, which are typically involved in GJT, are very severe. [22]…”
Section: Discussionmentioning
confidence: 99%
“…[119223340] In tumors with intracranial extension the rate of postoperative cranial nerve palsy ranges between 22% and 100%. [19202639] Mortality is significant, and can oscillate between 4.2% and 6.4% according to some studies.…”
Section: Discussionmentioning
confidence: 99%
“…Embolization is not considered curative due to formation of anastomotic blood vessels and is recommended only as a preparation for surgery. 16 Meanwhile, external-beam radiotherapy presents the risk of serious complications due to large fields size, as suggested by Li et al 17 Gamma Knife surgery emerged as an alternative during the last decade due to its minimal invasiveness and local tumor control rates comparable to surgical strategies, while preserving or even improving cranial nerve function. [4][5][6]18 Recently it has been reported that functioning PGLs also respond to stereotactic radiosurgery, and in particular to GKS, at both the biochemical and neuroradiological level.…”
Section: Surgical Intervention and Initial Surveillancementioning
confidence: 99%
“…Anderson Cancer Center from 1944 to 1964 consisted of administering 45 Gy to the tumor bed over 35 days. 32 It is important to note that the majority of patients included in these initial reports received radiation therapy following subtotal resection, and that radiation was not considered primary therapy outside of palliation for neoplasms believed to be inoperable. Despite its restricted use, these preliminary forms of radiotherapy were believed to be relatively effective; a meta-analysis of treatments performed prior to 1981 reported acceptable local control in 91% of patients, with low rates of morbidity.…”
Section: Evolution In Tumor Managementmentioning
confidence: 99%